Elevated blood pressure, heart rate and body temperature in mice lacking the XLαs protein of the Gnas locus is due to increased sympathetic tone. Issue 10 (12th July 2013) - Nunn, Nicolas; Feetham, Claire H.; Martin, Jennifer; Barrett‐Jolley, Richard; Plagge, Antonius
New Findings:   What is the central question of this study? Previously, we showed that Gnasxl knock‐out mice are lean and hypermetabolic, with increased sympathetic stimulation of adipose tissue. Do these mice also display elevated sympathetic cardiovascular tone? Is the brain glucagon‐like peptide‐1 system involved?   What is the main finding and its importance? Gnasxl knock‐outs have increased blood pressure, heart rate and body temperature. Heart rate variability analysis suggests an elevated sympathetic tone. The sympatholytic reserpine had stronger effects on blood pressure, heart rate and heart rate variability in knock‐out compared with wild‐type mice. Stimulation of the glucagon‐like peptide‐1 system inhibited parasympathetic tone to a similar extent in both genotypes, with a stronger associated increase in heart rate in knock‐outs. Deficiency of Gnasxl increases sympathetic cardiovascular tone. Imbalances of energy homeostasis are often associated with cardiovascular complications. Previous work has shown that Gnasxl ‐deficient mice have a lean and hypermetabolic phenotype, with increased sympathetic stimulation of adipose tissue. The Gnasxl transcript from the imprinted Gnas locus encodes the trimeric G‐protein subunit XLαs, which is expressed in brain regions that regulate energy homeostasis and sympathetic nervous system (SNS) activity. To determine whether Gnasxl knock‐out (KO) mice display additional SNS‐related phenotypes, we have now investigated the cardiovascular system. The Gnasxl KO mice were ∼20 mmHg hypertensive in comparison to wild‐type (WT) littermates ( P ≤ 0.05) and hypersensitive to the sympatholytic drug reserpine. Using telemetry, we detected an increased waking heart rate in conscious KOs (630 ± 10 versus 584 ± 12 beats min −1, KO versus WT, P ≤ 0.05). Body temperature was also elevated (38.1 ± 0.3 versus 36.9 ± 0.4°C, KO versus WT, P ≤ 0.05). To investigate autonomic nervous system influences, we used heart rate variability analyses. We empirically defined frequency power bands using atropine and reserpine and verified high‐frequency (HF) power and low‐frequency (LF) LF/HF power ratio to be indicators of parasympathetic and sympathetic activity, respectively. The LF/HF power ratio was greater in KOs and more sensitive to reserpine than in WTs, consistent with elevated SNS activity. In contrast, atropine and exendin‐4, a centrally acting agonist of the glucagon‐like peptide‐1 receptor, which influences cardiovascular physiology and metabolism, reduced HF power equally in both genotypes. This was associated with a greater increase in heart rate in KOs. Mild stress had a blunted effect on the LF/HF ratio in KOs consistent with elevated basal sympathetic activity. We conclude that XLαs is required for the inhibition of sympathetic outflow towards cardiovascular and metabolically relevant tissues.